Ozone: An Advanced Oxidation Technology to Enhance Sustainable Food Consumption through Mycotoxin Degradation. (2nd January 2022) - Sujayasree, O. J.; Chaitanya, A. K.; Bhoite, R.; Pandiselvam, R.; Kothakota, Anjineyulu; Gavahian, Mohsen; Mousavi Khaneghah, Amin
ABSTRACT: Mycotoxins are health-threatening fungal metabolites that have been found in several foods around the world. Although agricultural, transportation, and storage management strategies have been employed to reduce the production of mycotoxins, they are not effective in eliminating mycotoxins. In this context, the application of ozone has emerged for the degradation of mycotoxins. Ozone has a strong oxidation rate and generates more free radicals, which can counter the functional groups of the mycotoxin by changing their molecular structures and forming products having lower molecular weight reduced number of double bonds, and reduced toxicity. Research indicates that ozone could be able to destroy mycotoxins without leaving any residues in the commodities. The ozone processing parameters, surface and nutritional properties of food, and fungal species are the primary determinants affecting the processing efficacy. Ozone can contribute to sustainable food consumption through mycotoxin degradation to achieve sustainable development goals (SDGs).